Gathering Voices: Thomas Jefferson and Native America ... - Mason, Merrill; Marsh, Diana E. (American Philosophical Society News, 2016)
This spring, the American philosophical society opened its third in a series of exhi- bitions on Thomas Jefferson. Gathering Voices: Thomas Jefferson and Native America explores Jefferson’s effort to collect native languages and its legacy at the APS.There are a num- ber of “firsts”in Gathering Voices. it marks the first time the Aps Museum has displayed one of the Library’s largest collections—the papers, photographs, and audio recordings from some 270 native American and indigenous cultures. it is also the first time the Museum invited two native advisors— Margaret Bruchac (Abenaki) and richard hill, sr. (Tuscarora)—to work with our museum team.Thanks to the newly founded Center for native American and indigenous research (CNAIR), the exhibition piloted a consultative process with native communities whose materials are featured in Gathering Voices. The show also includes some of the Museum’s most extensive multimedia features, including an animated map projection, two interactive touch-screen stations, and ...